Pengaruh metode pelatihan yang bervariasi dengan ukuran kelas yang lebih kecil pada keterampilan berenang merangkak depan siswa - Arifin, Z; Mulyana, Boyke; Sutresna, Nina; Subarjah, Herman; Wahyudin Pratama, Kukuh (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2024)
However, the swimming learning process sometimes generalizes these abilities. The purpose of this study was to reveal the effect of varied training methods with smaller class sizes on students' front crawl swimming skills. The research used an experiment with a one-group pre-test-post-test design. The study population was 93 students, they take swimming lessons at the Sports Education Study Program, Garut University the 2022/2023 Academic Year. The sampling technique uses purposive sampling. The sample that reached the criteria was 22 students. The research instrument used a front crawl swimming skills test. Research procedure - giving treatment with varied methods with smaller class sizes. The data analysis technique uses Paired Sample t Test. Treatment with varied lesson delivery with smaller class sizes obtained sig values. (2-tailed) of 0.000. Based on the results of the research, findings revealed the value of sig. (2-tailed) obtained is 0.000. The score was lower than 0.05, so it was concluded that the method's effect varied with smaller class sizes on students' swimming skills on the front crawling swimming skills. The conclusion of this study is that using classroom settings and methods can affect swimming skills and front crawling style.